Metastasizing (Malignant) Ameloblastoma: Review of a Unique Histopathologic Entity and Report of Mayo Clinic Experience - Van Dam, Scott D.; Unni, Krishnan K.; Keller, Eugene E. (Journal of oral and maxillofacial surgery, 2010)
To provide a comprehensive review of metastasizing (malignant) ameloblastoma, establish a new baseline of valid cases using histologic criteria and minimum documentation, and report 3 cases from the Mayo Clinic files. Ninety-eight original reports of “metastasizing,” “malignant,” or “atypical” ameloblastoma were reviewed. The following data were gathered for reports that demonstrated well-differentiated ameloblastoma at the metastatic site: gender, ethnicity, age at time of primary tumor diagnosis, histologic pattern of primary tumor, anatomic sites of primary and metastatic tumors, interval from diagnosis of primary to diagnosis of metastasis, number of recurrences preceding metastasis, treatment responses to radiation and/or chemotherapy, presence of hypercalcemia, and length of survival after metastasis. Twenty-seven valid reports of metastasizing (malignant) ameloblastoma were identified; 81% originated in the mandible, recurring on average 4 times before metastasis. Lungs were the initial site of metastasis in 78% of reports, of which 71% were bilateral. The average time from diagnosis of primary to metastasis was 18 years. Over half of the patients were alive and had survived an average of 10 years since diagnosis of metastasis. Those patients who had succumbed to their disease had an average survival time of 3 years after diagnosis of metastasis. Metastasis of well-differentiated ameloblastoma occurs more rarely than previously believed. Metastasis to the lungs bilaterally, by the hematogenous route, usually follows multiple failed attempts at primary tumor control. The absence of malignant cytologic transformation correlates with relatively indolent metastatic site growth. Treatment of metastasizing (malignant) ameloblastoma should include close observation, thoracotomy with wedge resections, or experimental chemotherapeutic combinations.